One dimensional graphene nanoscroll-wrapped MnO nanoparticles for high-performance lithium ion hybrid capacitors. Issue 10 (11th February 2021) - Yang, Bingjun; Chen, Jiangtao; Liu, Bao; Ding, Yunxia; Tang, Yu; Yan, Xingbin
Abstract : We demonstrate a simple strategy for the preparation of 1D graphene nanoscroll wrapped MnO nanoparticles (GNS@MnO) as high-rate anode materials for lithium ion hybrid capacitors. Abstract : Lithium ion hybrid capacitors (LIHCs) have high power density and high energy density. One of the biggest problems in LIHCs is the kinetics mismatch of a battery-type anode and capacitive cathode due to relatively slow Li + reaction kinetics compared to fast ion adsorption/desorption behavior. Here, to address this challenge, an efficient strategy was proposed to prepare a one dimensional (1D) graphene nanoscroll wrapped MnO nanoparticle (GNS@MnO) material by a simple freeze-drying process followed by annealing treatment. The topological end-opening architecture of the GNS and the wrapping of graphene layers facilitate fast Li + diffusion and electron transfer. As an anode material of lithium ion batteries (LIBs), the optimized GNS@MnO-600 electrode exhibits outstanding performance for Li + ion storage with a high specific capacity of 437 mA h g −1 even at 5.0 A g −1 . The constructed LIHC based on the GNS@MnO-600 anode and 3D framework activated carbon (3DFAC) with a high specific surface area delivered a high energy density of 197 W h kg −1 at 235 W kg −1 . Even at a high power density of 23.5 kW kg −1, a high energy density of 114 W h kg −1 is still maintained, as well as a long cycling life (84.8% capacity retention after 3000 cycles). We believe that this highly efficient 1D GNS wrapping strategy provides a novel design concept for the construction of fast kinetics anode materials for LIBs and LIHCs.